2013
DOI: 10.1016/j.jana.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Support, Stigma, Health, Coping, and Quality of Life in Older Gay Men With HIV

Abstract: As life expectancy for persons living with HIV has increased due to antiretroviral therapy, quality of life (QOL) has become an emerging issue for older gay men with HIV, who comprise more than 50% of older adults living with HIV in the United States. The purpose of this study was to determine predictors of QOL in older gay men with HIV. Sixty gay men ages 50-65 participated. Age, social support, and problem-focused coping were significantly and positively correlated with QOL, while medical comorbidities, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 1 publication
4
41
0
8
Order By: Relevance
“…Despite these efforts, women recognized that they were aging, and some worried that they may run out of treatment options or that their aging bodies may just “give out” in response to the stress of managing HIV over time. These findings are consistent with recent studies that have examined aging among older PLWHA and highlight the importance of concepts such as resilience, optimism, and problem-focused coping to facilitate successful aging and better quality of life (Emlet et al, 2011; Moore et al, 2013; Slater et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…Despite these efforts, women recognized that they were aging, and some worried that they may run out of treatment options or that their aging bodies may just “give out” in response to the stress of managing HIV over time. These findings are consistent with recent studies that have examined aging among older PLWHA and highlight the importance of concepts such as resilience, optimism, and problem-focused coping to facilitate successful aging and better quality of life (Emlet et al, 2011; Moore et al, 2013; Slater et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…This result is important because both emotional and instrumental support are significant variables to achieve better quality of life. 18 The averages on emotional social support were slightly higher than the ones from the instrumental social support. A similar fact was observed in a research with caregivers of children and adolescents living with HIV/AIDS, which indicated satisfaction with the social support received, especially emotional, as opposed to the instrumental support, which covered financial aid and help in practical and operational aspects of everyday life.…”
Section: 14mentioning
confidence: 85%
“…Additionally, disentangling the impact of HIV as a health condition and as a social determinant of health can be challenging, as the effects may be overlapping. As a social determinant, HIV-related stigma has been negatively associated with quality of life (Slater et al, 2012), and HIV-related bereavement has been shown to influence mental health (Wight et al, 2012).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%